Bay of Piran or Bay of Savudrija? An example of problematic treatment of geographical names - Kladnik, Drago; Pipan, Primož (Acta geographica Slovenica, 2008)
The established geographical name Bay of Piran refers to the largest bay in the Gulf of Trieste at the extreme north end of the Adriatic Sea. After the collapse of Yugoslavia and the emergence of independent countries demarcated along the borders of the former Yugoslav republics, the previously undemarcated body of water between Slovenia and Croatia became the focus of a border dispute between the two countries. One of the basic principles of proper treatment of geographical names is not to change established and widely used names. The name ‘Bay of Piran’ (Sln. Piranski zaliv, Cro. Piranski zaljev) is derived from the Italian name Vallone di Pirano ‘Bay of Piran’, which replaced the Italian name Valle di Sicciole ‘Bay of Sečovlje’ (as well as Ital. Valle di Siciole, Sln. Sečoveljski zaliv) a century and half ago. This in turn was established towards the end of the 18th century, replacing the Italian name Largon ‘Broad’ or Golfo Largone ‘Broad Bay’. Since 2000 there have been Croatian attempts to establish the completely new name ‘Bay of Savudrija’ (Cro. Savudrijska vala, Sln. Savudrijski zaliv).